Optimization of Solar Module Encapsulant Lamination by Optical Constant Determination of Ethylene-Vinyl Acetate - Bing-Mau Chen; Cheng-Yu Peng; Ju-Lu Cho; Glen Andrew Porter (International Journal of Photoenergy)
This investigation elucidates the physical properties of ethylene-vinyl acetate (EVA) used in the lamination process of module encapsulation and the module performance from the optical transmission to the photoelectric power. In module encapsulation, the effects of the lamination parameters on the module performance, transmittance, and stack adhesion have been considered as they were found to influence the reliability of the module. The determination of the optical constants of EVA may serve as a nondestructive analytical method for optimizing the module encapsulation, on the basis of its effects on the optical transmittance, gel content, peel strength, and performance power.